Assessment Results of Dental Students' Knowledge about Bisphosphonates and Bisphosphonate-Related Osteonecrosis of the Jaw - Greta Sereikaite; Vesta Guzeviciene; Gabriele Peceliunaite; Povilas Daugela; Gintaras Juodzbalys (eJournal of Oral Maxillofacial Research, 2023)
Objectives: The aim of this cross-sectional study is to evaluate Lithuanian fourth- and fifth-year dental students' knowledge about bisphosphonates and bisphosphonate-related osteonecrosis of the jaw.